An Unusual Case of Aneurysmal Bone Cyst Involving Both Middle and Posterior Fossa Skull Base - Valsangkar, Shonali; Kharosekar, Hrushikesh; Velho, Vernon (Indian Journal of Neurosurgery, 2016)
Aneurysmal bone cyst (ABC) is a benign osteolytic bony lesion that can be locally destructive. The skull base is an uncommon location for this tumor with a reported incidence of 3 to 6%. In the literature, we found only 11 cases of skull base ABC reported till 2010, with only 2 involving the posterior cranial fossa skull base. This is the first case involving both the middle and posterior cranial fossa skull base reported till date.
Keywords: aneurysmal bone cyst; middle cranial fossa; posterior cranial fossa; clivus